Pemanfaatan Tanaman Aren (Arenga pinata Merr) Sebagai Bahan Dasar Sopi Di Kecamatan Kota Komba Kabupaten Manggarai Timur - Quirinus Ruek Da Suka; Paulus Un; Nixon Rammang (Wana Lestari, 2020)
One of the potential results of the forest in Komba village and Rongga Koe Village Office is sugar palm (Arenga pinnata Merr). It was the plants in which the people use for making sopi (traditional whiskey). This study aims to know the maintaining and the spread of Aren Palm (Arenga pinnata Merr ) plants. Bedise on that, this research also peretend to analyze the amount of sopi production and it’s profit. The number of respondents in this study are 32 respondents. They were randomly selected from 35 population samples. The collection of data was done by observation, interviews, and the library research. The data that were collected will be analyzed descriptively, by using its similarity to calculate the level of income and the level of profit. The results showed that the spread of sugar trees in the researched area was spread wildly and clumped which grew in areas with sloping topogragy and they were located around the water source area. The spread of sugar palm in clumps greatly facilitated the utilization process. Utilization of palm sugar at the research location only using the palm sugar sap to be made into sopi which is classified into 3 types of sopi businesses, namely raw sopi (tuak bakok), namely fermented sopi from sugar palm sap which is produced by each tapping palm sugar sap 25 liters per day from 6 palm trees, distilling sopi the first level produces 1 bottle of first class (bakar menyala), and 8 bottles of second class (Tuak Arak) as much as 8 bottles per distillation and the second level of distillation produces 22 bottles of first class sopi from the distillation of second class sopi in one distillation process. The usage of the three types of sopi gives advantages to each type of sopi. At the level of raw sopi business R/C Ratio 10.82>1, the first level refining business R/C Ratio 9.59>1, and the second level of sopi refining business R/C Ratio 1.59>1, where the R/C ratio value >1 indicates the business is profitable.